2009
DOI: 10.1186/1744-8069-5-55
|View full text |Cite
|
Sign up to set email alerts
|

Nociception-Induced Spatial and Temporal Plasticity of Synaptic Connection and Function in the Hippocampal Formation of Rats: a Multi-Electrode Array Recording

Abstract: BackgroundPain is known to be processed by a complex neural network (neuromatrix) in the brain. It is hypothesized that under pathological state, persistent or chronic pain can affect various higher brain functions through ascending pathways, leading to co-morbidities or mental disability of pain. However, so far the influences of pathological pain on the higher brain functions are less clear and this may hinder the advances in pain therapy. In the current study, we studied spatiotemporal plasticity of synapti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(69 citation statements)
references
References 97 publications
(154 reference statements)
5
64
0
Order By: Relevance
“…As expected, the negative-going LFPs evoked by PP stimulation at the site (asterisk, electrode #29, Fig. 3A) were mainly confined to the dendritic distribution areas of both granular and pyramidal neurons in the normal or saline control state [31] . The spread of the PP-evoked depolarization was clearly shown by 2-dimensional current source density (2D-CSD) imaging (Fig.…”
Section: Experimental Setupssupporting
confidence: 78%
See 3 more Smart Citations
“…As expected, the negative-going LFPs evoked by PP stimulation at the site (asterisk, electrode #29, Fig. 3A) were mainly confined to the dendritic distribution areas of both granular and pyramidal neurons in the normal or saline control state [31] . The spread of the PP-evoked depolarization was clearly shown by 2-dimensional current source density (2D-CSD) imaging (Fig.…”
Section: Experimental Setupssupporting
confidence: 78%
“…To summarize, the though the latter at 100 µmol/L also significantly reduced the whole network response (see Fig. 5 of Zhao et al [31] ).…”
Section: Experimental Setupsmentioning
confidence: 76%
See 2 more Smart Citations
“…Wei, Xu, Qu, Milbrandt, & Zhuo (2000) first recorded a hippocampal reaction to peripheral noxious stimulations in adult rats. Zhao reported that in a bee venom‐induced persistent pain animal model, hippocampus LTP was remarkably enhanced (Zhao et al., 2009). In this study, we observed that LTP induced by HFS in the hippocampus CA1 region significantly increased in IBS‐like rats, which is in accordance with our previous data (Chen et al., 2014).…”
Section: Discussionmentioning
confidence: 99%